Fecal microbiota transplantation revealed the function of folic acid on reducing abdominal fat deposition in broiler chickens mediated by gut microbiota - Xiaoying Liu; Chaohui Wang; Yun Li; Yumeng Wang; Xi Sun; Qianggang Wang; Jiarui Luo; Wen Lv; Xiaojun Yang; Yanli Liu (Poultry Science, 2024)
ABSTRACT: Excess abdominal fat reduces carcass yield and feed conversion ratio, thereby resulting in significant economic losses in the poultry industry. Our previous study demonstrated that dietary addition of folic acid reduced fat deposition and changed gut microbiota and short-chain fatty acid. However, whether folic acid regulating abdominal fat deposition was mediated by gut microbiota was unclear. A total of 210 one-day-old broiler chickens were divided into 3 groups including the control (CON), folic acid (FA), and fecal microbiota transplantation (FMT) groups. From 14th day, broiler chickens in CON and FA groups were given perfusion administration with 1 mL diluent daily, while 1 mL fecal microbiota transplantation suspension from FA group prepared before was perfusion in FMT group receiving control diets. The result showed that abdominal fat percentage was significantly lower in FA and FMT groups when compared with CON group (P < 0.05). Morphology analysis revealed that the villus height of jejunum and ileum were significantly higher in FMT group (P < 0.05), and the villus height of jejunum was also significantly higher in FA group (P < 0.05), while the diameter and cross-sectional area (CSA) of adipocytes were significantly decreased in FA and FMT groups when compared with CON group (P < 0.05). Western blot results indicated that the expression levels of FOXO1 and PLIN1 in FMT group were significantly increased (P < 0.05), whereas the expression levels of PPARγ, C/EBPα, and FABP4 were significantly decreased (P < 0.05). Additionally, the Chao1, Observed-species, Shannon and Simpson indexes in FA and FMT groups were significantly higher (P < 0.05), but the microbiota were similar between FMT and FA groups (P < 0.05). LEfSe analysis determined that Lactobacillus, Clostridium and Dehalobacterium were found to be predominant in FA group, while Oscillospira, Shigella, and Streptococcus were the dominant microflora in FMT group. Furthermore, these cecal microbiota were mostly involved in infectious disease, cellular community prokaryotes, cell motility and signal transduction in FA group (P < 0.05), whereas functional capacities involved in signal transduction, cell motility, infectious disease and environment adaptation were enriched significantly of cecal microbiota in FMT group (P < 0.05). In summary, both fecal microbiota transplantation from the broiler chickens of dietary added folic acid and dietary folic acid addition effectively reduced abdominal fat deposition, indicating that the regulatory effect of folic acid on abdominal fat deposition was mediated partly by gut microbiota in broiler chickens.